KUALITAS PELAYANAN COMMUTER LINE SERVICE QUALITY OF COMMUTER LINE - Deslida Saidah (Institut Transportasi dan Logistik Trisakti, 2017)
The increase in number of passengers is influenced by schedule, price, and improved infrastructure and facilities. The study aims to identify the effect of new schedule and price on service quality. The study used non probability sampling method to acquire data from passengers. Regression was used to analyze the data collected. Hypothesis test show coesfficient of schedule towards service quality is 0.568 while tariff affects service quality with a coefficient of 0.535. The study suggests improvement on scheduling and tariff.